In silico study of Thiourea derivatives as potential epidermal growth factor receptor inhibitors - Roslan, Norashikin; Abd Halim, Khairul Bariyyah; Muhamad Bunnori, Noraslinda; Mohd Aluwi, Mohd Fadhlizil Fasihi; Kassim, Karimah; Ngah, Nurziana (World Scientific Publishing, 2023)
Over the years, the escalation of cancer cases has been linked to the resistance, less selectivity, and toxicity of available anticancer drugs to normal cells. Therefore, continuous efforts are necessary to find new anticancer drugs with high selectivity of epidermal growth factor receptor tyrosine kinase (EGFR-TK) as a therapeutic target. The EGFR-TK protein has a crucial role in cell proliferation and cancer progression. With about 30% of cancer cases involved with the protein, it has piqued the interest as a therapeutic target. The potential of theoretically designed thiourea derivatives as anticancer agents in this report was evaluated against EGFR-TK via in silico techniques, including molecular docking (AutoDock Vina), molecular dynamics simulations (GROMACS), pharmacokinetics, and drug-likeness properties (SwissADME and Molinspiration). New hybrid molecules of the thiourea derivative moiety were designed in this study based on the fragment-based drug discovery and linked with diverse pharmacophoric fragments with reported anticancer potential ( ) and the modification of the methyl position on phenyl ring ( ). These fragments include pyridine, thiophene, furan, pyrrole and styrene groups. Out of 15 compounds, compound 13 displayed the most potent inhibitory activity, with the lowest binding affinity in docking of 8.7 kcal/mol compared to the positive control erlotinib of 6.7 kcal/mol. Our molecular dynamics (MD) simulations revealed that molecule 13, comprising styrene and 2-methylphenyl substituents on and, respectively, showed adequate compactness, uniqueness and satisfactory stability. Subsequently, the absorption, distribution, metabolism, excretion and toxicity (ADMET) properties and drug-likeness properties also indicate that this theoretically designed inhibitor ( 13) is less toxic and contains high druggable properties. Thus, compound 13 could be promising against EGFR-TK.